Antifouling polyester film for solar cell front panel and preparation method of antifouling polyester film

The two-layer structure anti-fouling polyester film prepared through multi-layer co-extrusion process solves the problem of poor adhesion of anti-fouling coating on the composite front panel, and achieves the effective anti-fouling and light transmission performance improvement of the solar cell front panel. Suitable for composite and glass front panels, reducing maintenance costs.

CN119242195APending Publication Date: 2025-01-03JIANGSU SHUANGXING COLOR PLASTIC NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311782397.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The anti-fouling coating of the existing solar cell front panel has poor adhesion on the composite front panel, which is easy to scratch, and cannot effectively prevent the accumulation of dust and sludge, resulting in reduced power generation efficiency and high cost, and the existing anti-fouling coating cannot be used. Tempered glass front plate at high temperature.

Method used

A two-layer structure anti-fouling polyester film prepared by multi-layer co-extrusion process. The surface layer is made of polyester slices with anti-fouling masterbatch added. The bottom layer is made of polyester slices without anti-fouling masterbatch added. The surface is coated with an adhesive layer to form a peelable antifouling layer structure, and the antifouling performance is improved by using nanomodified aluminum sulfate particles and low-surface energy materials.

Benefits of technology

It realizes effective anti-fouling function for solar cell front panels, can be easily peeled and replaced from the front panel, has excellent light transmission performance and uniformity, and is suitable for composite front panels and glass front panels, reducing maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242195A_ABST
    Figure CN119242195A_ABST
Patent Text Reader

Abstract

The invention discloses an antifouling polyester film for a solar cell front panel, the antifouling polyester film is used for being attached to the surface of one side, facing the sun, of a front panel body of the solar cell front panel in a peelable mode, and the antifouling polyester film is a film which is of a two-layer structure and is manufactured through a multi-layer co-extrusion technology. Comprising a surface layer facing the sun and a bottom layer adjacent to the front plate body, and the bottom layer is connected with the front plate body through an adhesive layer. The antifouling polyester film is used as the outermost layer structure of the solar cell front panel, can provide an antifouling function, can be conveniently peeled off from the front panel main body for replacement, and also has excellent light transmission performance and good uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to an antifouling layer of a solar cell front plate composited with a polymer material, and more particularly to an antifouling polyester film for a solar cell front plate and a preparation method thereof. Background Art

[0002] Solar cell modules are usually composed of front panels, packaging materials, solar cells, back panels, etc. The back panels are used to protect solar cell modules from water vapor erosion and internal oxidation of the modules, and must have reliable insulation, water resistance, aging resistance, high and low temperature resistance, corrosion resistance, etc. The front panels are mostly made of glass, which has high strength and good light transmittance.

[0003] CN 103627226 B discloses a highly anti-reflective and highly weather-resistant solar glass anti-reflective and anti-fouling coating and a production method thereof. The prior art mentions that an anti-reflective layer needs to be provided on the glass front plate to improve the light transmittance of the glass front plate, but there is a contradiction between the weather resistance and anti-reflective layer, so the prior art proposes an anti-reflective coating for solar glass, which is composed of alkaline silica sol, polymerized silica, aluminum dihydrogen phosphate, silicon phosphate, phosphoric acid, a surfactant and deionized water. The solar glass anti-reflective coating of the prior art uses silicon phosphate as an antistatic agent, so that the prepared coating has antistatic properties and dust or pollutants are not easy to accumulate, and has anti-fouling properties.

[0004] CN 105152546 B discloses a transparent antifouling coating material for glass, a transparent antifouling coating and a preparation method thereof, wherein the material comprises a mixed dispersion of fumed silica nanoparticles, a low surface energy binder and a solvent. The coating prepared from the antifouling coating material of the prior art has hydrophobicity, transparency and antifouling properties. However, the antifouling coating only works on sewage raindrops and the like, and has no effect on the adsorption of dust by solar panels.

[0005] On the other hand, in the prior art, there are not only glass front panels, but also front panels made of polymer composite materials. Composite front panels have the advantages of being light and bendable, but cannot be tempered at high temperatures like glass front panels, so the antifouling coating disclosed in CN 103627226 B cannot be applied to composite front panels. The antifouling coating material disclosed in CN 105152546 B has poor adhesion and can be quickly wiped off by scrubbing, so it is not suitable for solar cell front panels used outdoors.

[0006] Furthermore, solar cells are usually installed outdoors in sunny areas, where there is usually a lack of water sources. It is very difficult to wash the surface of solar cells with water. In many cases, the only way is to use tools to dry-rub the front panel of the solar cell. The anti-fouling coating on the surface of the front panel is easily scratched, and more dust and mud will accumulate where the coating is missing. The scratched coating is difficult to remove, especially the coating on the surface of the composite front panel cannot be peeled off. The entire front panel can only be replaced, which is very costly. In most cases, people are forced to accept the reality of reduced power generation efficiency until the battery life ends. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide an antifouling polyester film for a solar cell front plate and a preparation method thereof, so as to reduce or avoid the above-mentioned problems.

[0008] In order to solve the above-mentioned technical problems, the present application proposes an anti-fouling polyester film for a solar cell front panel, which is used to be removably attached to the surface of the front panel body of the solar cell front panel facing the sun, wherein the anti-fouling polyester film is a two-layer structure film made by a multi-layer co-extrusion process, including a surface layer facing the sun and a bottom layer arranged adjacent to the front panel body, and the bottom layer is connected to the front panel body through an adhesive layer.

[0009] Preferably, the outer side of the adhesive layer is covered with a release film.

[0010] Preferably, the surface layer is made of polyester chips to which antifouling masterbatch is added; and the bottom layer is made of polyester chips to which antifouling masterbatch is not added.

[0011] Preferably, the surface layer and the bottom layer are made of the same polyester chips.

[0012] Preferably, the antifouling masterbatch is composed of the following components in parts by weight: 70-80 parts by weight of a polyester carrier, 10-20 parts by weight of hexadecyltrimethylammonium bromide, 15-25 parts by weight of dodecylbis(hydroxyethyl)methylammonium chloride, 5-15 parts by weight of heptadecafluorodecyltriethoxysilane and 5-15 parts by weight of nano-modified aluminum sulfate particles.

[0013] The present application also proposes a method for preparing the above-mentioned antifouling polyester film, comprising the following steps: adding the prepared antifouling masterbatch to polyester chips as the surface layer raw material at a ratio of 10wt%-30wt% of the total mass of the surface layer, using 100wt% of the polyester chips as the bottom layer raw material, obtaining the surface layer and the bottom layer through a multi-layer co-extrusion process, and finally coating an adhesive layer on the surface of the bottom layer to prepare the antifouling polyester film.

[0014] Preferably, the method further comprises the step of preparing an antifouling masterbatch: uniformly mixing 70-80 parts by weight of a polyester carrier, 10-20 parts by weight of hexadecyltrimethylammonium bromide, 15-25 parts by weight of dodecylbis(hydroxyethyl)methylammonium chloride, 5-15 parts by weight of heptadecafluorodecyltriethoxysilane and 5-15 parts by weight of nano-modified aluminum sulfate particles, and then extruding and granulating to obtain the antifouling masterbatch.

[0015] Preferably, the method further comprises the step of preparing nano-modified aluminum sulfate particles: tetraethyl silicate and ethanol are mixed and stirred in a mass ratio of 1:1.2, 20% hydrochloric acid is added dropwise, the pH value is adjusted to 2, and the mixture is stirred at 60°C for 1-1.5 hours to obtain a liquid mixture, 1000 parts by weight of the liquid mixture is taken, 10-100 parts by weight of nano-aluminum sulfate is added, and the mixture is stirred for 60-120 minutes to obtain a dispersed mixture; the dispersed mixture is sprayed with freeze-drying, and particles with a particle size of 10-20 nm are selected through screening to obtain nano-modified aluminum sulfate particles.

[0016] The anti-fouling polyester film of the present application serves as the outermost layer structure of the solar cell front panel, can provide anti-fouling function, and can be easily peeled off from the front panel body for replacement. In addition, the anti-fouling polyester film of the present application also has excellent light transmittance and good uniformity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The following drawings are only intended to illustrate and explain the present application, and do not limit the scope of the present application.

[0018] Figure 1 A schematic structural diagram of a solar cell front panel according to a specific embodiment of the present application is shown.

[0019] Figure 2 A schematic structural diagram of a solar cell front panel according to another specific embodiment of the present application is shown.

[0020] Figure 3 A schematic structural diagram of an antifouling polyester film according to a specific embodiment of the present application is shown. DETAILED DESCRIPTION

[0021] In order to have a clearer understanding of the technical features, purposes and effects of the present application, the specific implementation of the present application is now described with reference to the accompanying drawings, wherein the same components are numbered the same.

[0022] In view of the problems existing in the prior art of applying an antifouling coating on the front panel of a solar cell, the present application proposes an antifouling polyester film for the front panel of a solar cell. The antifouling polyester film, as the outermost layer of the front panel of the solar cell, can provide an antifouling function and can be easily peeled off from the front panel body for replacement. That is, the antifouling polyester film of the present application is used to be peelably attached to the surface of the front panel body of the solar cell front panel facing the sun.

[0023] Figure 1 A schematic diagram of the structure of a solar cell front panel according to a specific embodiment of the present application is shown. Figure 1 In the specific embodiment shown, the solar cell front plate comprises at least one front plate body 1 made of glass, and the anti-fouling polyester film 2 of the present application is attached to the surface of the front plate body 1 facing the sun.

[0024] exist Figure 1 In the specific embodiment shown, the front panel body 1 has only a single layer of glass with a thickness of 100-1000 μm. Of course, those skilled in the art should understand that other functional coatings or protective films and other structures can be attached to one or both sides of the surface of the glass front panel body 1 as needed.

[0025] Figure 2 A schematic diagram of the structure of a solar cell front panel according to another specific embodiment of the present application is shown. Figure 2 In the specific embodiment shown, the solar cell front plate comprises at least a front plate body 1 composed of multiple layers of composite materials, and the antifouling polyester film 2 of the present application is attached to the surface of the front plate body 1 facing the sun.

[0026] exist Figure 2 In the specific embodiment shown, the front panel body 1 composed of the composite material at least includes a PET film 10, and the PET film 10 is bonded to a fluorocarbon resin protective film 30 through an adhesive layer 20. The fluorocarbon resin protective film 30 is arranged adjacent to one side of the antifouling polyester film 2, and the PET film 10 provides a supporting skeleton for the entire front panel. The inner side of the PET film 10 can be further provided with a weather-resistant coating or bonded with a protective layer. The fluorocarbon resin includes but is not limited to polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polytrifluorochloroethylene (FEVE) and / or polyvinyl fluoride (PVF). In a specific embodiment, the thickness of the PET film 10 is 100-200μm, the thickness of the adhesive layer 20 is 3-5μm, and the thickness of the fluorocarbon resin protective film 30 is 10-20μm.

[0027] Figure 3 The schematic diagram of the structure of the antifouling polyester film according to a specific embodiment of the present application is shown. Figure 3In the specific embodiment shown, the antifouling polyester film 2 is a two-layer film made by a multi-layer co-extrusion process, including a surface layer 21 facing the sun and a bottom layer 22 arranged adjacent to the front plate body 1, and the bottom layer 22 is connected to the front plate body 1 through an adhesive layer 23. Figure 2 In the front panel main structure shown, the adhesive layer 23 is connected to the fluorocarbon resin protective film 30. Of course, as an independent anti-fouling polyester film 2, before it is produced and assembled on the front panel main body 1, it is necessary to cover the adhesive layer 23 with a release film 24 to protect the adhesive layer 23. When the anti-fouling polyester film 2 needs to be assembled on the front panel main body 1, the release film 24 needs to be removed, and then the adhesive layer 23 is attached to the surface of the front panel main body 1. Figure 2 The structure is that the adhesive layer 23 is attached to the surface of the fluorocarbon resin protective film 30. The adhesive layer 23 can be any suitable transparent adhesive in the prior art, such as acrylic resin adhesive or polyurethane resin adhesive.

[0028] Since the surface energy of the fluorocarbon resin protective film 30 is very low, the bonding force between the adhesive layer 23 and the fluorocarbon resin protective film 30 is relatively weak, and the anti-fouling polyester film 2 of the present application together with the adhesive layer 23 can be peeled off from the surface of the fluorocarbon resin protective film 30 when necessary without adding any release agent. For example, when the anti-fouling polyester film 2 is scratched or aged, the anti-fouling polyester film 2 can be easily peeled off from the front panel body for replacement, thereby avoiding the problems existing in applying the anti-fouling coating on the front panel of the solar cell.

[0029] When it is necessary to apply the antifouling polyester film 2 of the present application to Figure 1 When the antifouling polyester film 2 is attached to the front plate body 1 made of glass as shown, a certain amount of release agent needs to be added to the adhesive layer 23 so that the antifouling polyester film 2 can be smoothly peeled off from the glass surface. For example, any existing suitable transparent release agent can be added. Alternatively, in a specific embodiment of the present application, the adhesive layer can use a heat-separable adhesive, for example, an adhesive used in electronic devices in the prior art (such as an adhesive for bonding mobile phone screens) can be used. When peeling is required, the antifouling polyester film 2 can be separated from the front plate body 1 by heating.

[0030] Furthermore, the surface layer 21 of the antifouling polyester film 2 is prepared from polyester chips to which an antifouling masterbatch is added, and the bottom layer 22 is prepared from polyester chips to which no antifouling masterbatch is added. In a preferred embodiment, the surface layer 21 and the bottom layer 22 use the same polyester chips. Due to the need for antifouling, an antifouling masterbatch with low surface energy is added to the surface layer 21. If there is no bottom layer 22, the adhesive layer 23 cannot be firmly connected to the surface layer 21. When it is necessary to peel off the antifouling polyester film 2, the adhesive layer 23 may remain on the surface of the fluorocarbon resin protective film 30. In this case, the present application provides a bottom layer 22 with normal adhesion in a multi-layer co-extrusion manner, so that the adhesive layer 23 can be peeled off together with the bottom layer 22 without glue pulling or residue.

[0031] The polyester slice of the present application can be formed by polycondensation of diprotic acid and diol.Diprotic acid components include but are not limited to terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 3,4'-diphenyl ether dicarboxylic acid, hexahydrophthalic acid, 2,7-naphthalene dicarboxylic acid, phthalic acid, 4,4'-methylene dibenzoic acid, oxalic acid, malonic acid, succinic acid, methyl succinic acid, glutaric acid, adipic acid, 3-methyl adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,11-undecanedicarboxylic acid, 1,10-decanedicarboxylic acid, undecane dioic acid, 1,12-dodecane dioic acid, hexadecanedicarboxylic acid, docosane dioic acid, tetracosane dioic acid, dimer acid, 1,4-cyclohexane dicarboxylic acid, 1,3-cyclohexane dicarboxylic acid, 1,1-cyclohexane diacetic acid, fumaric acid and maleic acid.These acids can be used alone or in combination. For example, the diol component includes, but is not limited to, ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, diethylene glycol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, dimer glycol, diethylene glycol, triethylene glycol, poly(ethylene ether) glycol, poly(tetramethylene ether) glycol, branched glycol, hexanediol or a combination or derivative thereof, 1,4-cyclohexanedimethanol, 1,5-pentanediol, 3-methyl-2,4-pentanediol, neopentyl glycol, 2-methyl-1,4-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 2,5-ethyl-1,3-hexanediol, 2,2-diethyl-1,3-propylene glycol, 1,3-hexanediol. These alcohols can also be used alone or in combination.

[0032] The polyester slice of the present application can also be formed by hydroxycarboxylic acid and its ester-forming derivative or cyclic ester.Hydroxycarboxylic acid components include but are not limited to lactic acid, citric acid, malic acid, tartaric acid, glycolic acid, 3-hydroxybutyric acid, p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, 4-hydroxycyclohexanecarboxylic acid, etc.The ester-forming derivative of hydroxycarboxylic acid includes but is not limited to dimethyl terephthalate, dimethyl isophthalate, 2,6-dimethyl naphthalene dicarboxylate, 3,4'-diphenyl ether dicarboxylic acid dimethyl ester, hexahydrophthalic acid dimethyl ester, 2,7-dimethyl naphthalene dicarboxylate, dimethyl phthalate, 4,4'-methylenebisbenzoic acid dimethyl ester, dimethyl oxalate, dimethyl malonate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, dimethyl azelaic acid, 1,3-cyclohexane dicarboxylic acid dimethyl ester and 5-sulfo dimethyl isophthalate. These components can be used alone or in combination. In addition, cyclic esters include, but are not limited to, ε-caprolactone, β-propiolactone, β-methyl-β-propiolactone, δ-valerolactone, glycolide, lactide, etc. Cyclic esters can also be used alone or in combination.

[0033] In a specific embodiment, the polyester chips used in the present application are preferably polyethylene terephthalate (PET), polybutylene terephthalate, polytrimethylene terephthalate, poly-1,4-cyclohexanedimethanol terephthalate (PCT), polyethylene naphthalate, polybutylene naphthalate, polytrimethylene naphthalate and copolymers thereof. Polyethylene terephthalate (PET) and copolymers thereof are particularly preferred.

[0034] The preparation method of the polyester chips of the present application takes PET as an example. The preferred preparation method comprises the following steps: first, terephthalic acid or dimethyl terephthalate is subjected to esterification or transesterification reaction with ethylene glycol to obtain dihydroxyethyl terephthalate. Then, a catalyst is used to carry out polycondensation reaction under high temperature and vacuum conditions to polycondense dihydroxyethyl terephthalate into polyethylene terephthalate (PET). In a specific embodiment, terephthalic acid, ethylene glycol, cyclohexanedimethanol, a catalyst and a thermal stabilizer can be used as raw materials for esterification reaction; or terephthalic acid, ethylene glycol, isophthalic acid, a catalyst and a thermal stabilizer can be used as raw materials for esterification reaction. The catalyst can be selected from any one of Ti / Si non-heavy metal catalysts and antimony trioxide, and the amount added is 0.01 to 0.09% of the mass of the polyester. The heat stabilizer can be selected from phosphoric acid compounds, such as any one of phosphoric acid, phosphorous acid, polyphosphoric acid, trimethyl phosphate, triphenyl phosphate, and triethyl phosphate, and the added amount thereof is 0.0003 to 0.030% of the mass of the polyester.

[0035] In another specific embodiment of the present application, the polyester chips of the present application can be prepared by the following method: 5.0 kg of terephthalic acid, 2.2 kg of ethylene glycol, and 1.10 g of germanium dioxide are added to a 20 L general polymerization reactor, and an esterification reaction is carried out at 230-265 ° C and 0.2-0.3 MPa (gauge pressure). When the water output reaches 1200 ml, the pressure is released to normal pressure, 1.025 g of triphenyl phosphate is added, and the mixture is stirred at normal pressure for 10 minutes. The temperature is increased and the pressure is reduced to below 280 ° C and the pressure is lower than 100 Pa. After 1 to 3 hours of reaction, the mixture is extruded, pelletized, and dried to finally obtain polyester chips.

[0036] Further, the antifouling masterbatch of the antifouling polyester film 2 of the present application is composed of the following components in parts by weight: 70-80 parts by weight of a polyester carrier, 10-20 parts by weight of hexadecyltrimethylammonium bromide, 15-25 parts by weight of dodecylbis(hydroxyethyl)methylammonium chloride, 5-15 parts by weight of heptadecafluorodecyltriethoxysilane, and 5-15 parts by weight of nano-modified aluminum sulfate particles. After the components of the antifouling masterbatch of the present application are uniformly mixed, the antifouling masterbatch can be obtained by extruding and granulating using equipment such as an extruder.

[0037] The preparation steps of the nano-modified aluminum sulfate particles are as follows: tetraethyl silicate and ethanol are mixed and stirred in a mass ratio of 1:1.2, 20% hydrochloric acid is added dropwise, the pH value is adjusted to 2, and the mixture is stirred at 60°C for 1-1.5 hours to obtain a liquid mixture, 1000 parts by weight of the liquid mixture is taken, 10-100 parts by weight of nano-aluminum sulfate is added, and the mixture is stirred for 60-120 minutes to fully mix and obtain a dispersed mixture; the dispersed mixture is subjected to freeze-drying spray, and particles with a particle size of 10-20nm are screened to obtain nano-modified aluminum sulfate particles. The nano-modified particles are core-shell structures coated with silicon dioxide, and the solvent is fully removed by freeze-drying spray to improve the weather resistance of the subsequent coating. Relatively speaking, the gel coating treatment scheme of the prior art is removed by evaporation, and solvent residues are prone to occur, which has a great impact on performance.

[0038] The antifouling masterbatch can be added to the polyester chips as the surface layer raw material at a ratio of 10wt%-30wt% of the total mass of the surface layer, and 100wt% of the polyester chips are used as the bottom layer raw material, and the surface layer 21 and the bottom layer 22 are obtained by a multi-layer co-extrusion process, and finally the surface of the bottom layer 22 is coated with an adhesive layer 23 to prepare the antifouling polyester film 2 of the present application. Of course, a release film 24 can also be further covered on the surface of the adhesive layer 23 to provide protection for the adhesive layer 23.

[0039] Example

[0040] The components in the following examples are replaced by the following letters to simplify the table content.

[0041] Hexadecyltrimethylammonium bromide: A

[0042] Dodecyl bis(hydroxyethyl)methyl ammonium chloride: B

[0043] Heptadecafluorodecyltriethoxysilane: C

[0044] Nano-modified aluminum sulfate particles: D

[0045] In the following examples, PET was used as a polyester carrier to prepare an antifouling masterbatch.

[0046] The weight parts of each embodiment and comparative example are shown in the table below.

[0047] The antifouling masterbatches prepared in Examples 1-4 and Comparative Examples 1-4 were added to polyester chips at a ratio of 10wt%-30wt% of the total mass of the surface layer as the surface layer raw material, and 100wt% of the polyester chips were used as the bottom layer raw material, and a double-layer film consisting of a surface layer 21 and a bottom layer 22 was obtained by a multi-layer co-extrusion process. Then, an adhesive layer 23 was coated on the surface of the bottom layer 22, and finally, a release film 24 was covered on the surface of the adhesive layer 23, and the antifouling polyester films of Examples 5-8 and Comparative Examples 5-8 were prepared respectively, and the specific parameters were as follows.

[0048] Surface masterbatch ratio Surface thickness Bottom layer thickness Adhesive layer thickness Release film thickness Example 5 10wt% 10μm 10μm 5μm 25μm Example 6 15wt% 15μm 15μm 6μm 30μm Example 7 20wt% 20μm 20μm 7μm 40μm Example 8 30wt% 25μm 25μm 8μm 50μm Comparative Example 5 10wt% 10μm 10μm 5μm 25μm Comparative Example 6 15wt% 15μm 15μm 6μm 30μm Comparative Example 7 20wt% 20μm 20μm 7μm 40μm Comparative Example 8 30wt% 25μm 25μm 8μm 50μm

[0049] During the test, the release film 24 is removed, and the performance parameters of the antifouling polyester film actually used are tested as follows, wherein the transmittance test is the visible light transmittance.

[0050]

[0051] In addition, the prepared film was divided into regions, and the film pieces from different divided regions were cut to test the consistency of the film. The test showed that the performance difference rate of each film piece of the film of Examples 5-8 was less than 5%, while the surface energy difference rate of each film piece of the film of Comparative Examples 5-8 was relatively large, with the difference rates being 13%, 17%, 18%, and 16%, respectively. In addition, the difference rate of the contact angle of the surface layer exceeded 15%. The results show that the antifouling polyester film prepared by the preparation process of the present application has excellent light transmittance and good uniformity, indicating that the antifouling component of the present invention has good dispersibility and is particularly suitable for antifouling of solar cell front panels.

[0052] Those skilled in the art should understand that although the present application is described in the form of multiple embodiments, not every embodiment contains only one independent technical solution. Such description in the specification is only for the sake of clarity, and those skilled in the art should understand the specification as a whole and regard the technical solutions involved in each embodiment as being able to be combined into different embodiments to understand the scope of protection of the present application.

[0053] The above description is only an illustrative embodiment of the present application and is not intended to limit the scope of the present application. Any equivalent changes, modifications and combinations made by any technician in the field without departing from the concept and principle of the present application shall fall within the scope of protection of the present application.

Claims

1. An antifouling polyester film for a solar cell front sheet, which is used to be peelably attached to the surface of the front sheet main body of the solar cell front sheet facing the sun, characterized in that: The antifouling polyester film is a two-layer film made by a multi-layer co-extrusion process, including a surface layer facing the sun and a bottom layer arranged adjacent to the front plate body, and the bottom layer is connected to the front plate body through an adhesive layer.

2. The antifouling polyester film according to claim 1, characterized in that The outer side of the adhesive layer is covered with a release film.

3. The antifouling polyester film according to claim 1, characterized in that The surface layer is prepared from polyester chips to which antifouling masterbatch is added; and the bottom layer is prepared from polyester chips to which antifouling masterbatch is not added.

4. The antifouling polyester film according to claim 1, characterized in that The surface layer and the bottom layer are made of the same polyester chips.

5. The antifouling polyester film according to claim 3, characterized in that The antifouling masterbatch is composed of the following components in parts by weight: 70-80 parts by weight of a polyester carrier, 10-20 parts by weight of hexadecyltrimethylammonium bromide, 15-25 parts by weight of dodecylbishydroxyethylmethylammonium chloride, 5-15 parts by weight of heptadecafluorodecyltriethoxysilane and 5-15 parts by weight of nano-modified aluminum sulfate particles.

6. A method for preparing an antifouling polyester film as described in any one of claims 1 to 5, comprising the following steps: adding the prepared antifouling masterbatch to polyester chips as a surface layer raw material at a ratio of 10wt%-30wt% of the total mass of the surface layer, using 100wt% of the polyester chips as a bottom layer raw material, obtaining the surface layer and the bottom layer through a multi-layer co-extrusion process, and finally coating an adhesive layer on the surface of the bottom layer to prepare the antifouling polyester film.

7. The preparation method as claimed in claim 6 further comprises the step of preparing an antifouling masterbatch: uniformly mixing 70-80 parts by weight of a polyester carrier, 10-20 parts by weight of hexadecyltrimethylammonium bromide, 15-25 parts by weight of dodecylbis(hydroxyethyl)methylammonium chloride, 5-15 parts by weight of heptadecafluorodecyltriethoxysilane and 5-15 parts by weight of nano-modified aluminum sulfate particles, and then extruding and granulating to obtain the antifouling masterbatch.

8. The preparation method as claimed in claim 7, further comprising the steps of preparing the nano-modified aluminum sulfate particles: mixing tetraethyl silicate and ethanol in a mass ratio of 1:1.2, adding 20% ​​hydrochloric acid dropwise, adjusting the pH value to 2, stirring at 60°C for 1-1.5 hours to obtain a liquid mixture, taking 1000 parts by weight of the liquid mixture, adding 10-100 parts by weight of nano-aluminum sulfate, stirring for 60-120 minutes to fully mix to obtain a dispersed mixture; subjecting the dispersed mixture to freeze-drying spraying, and screening to obtain particles with a particle size of 10-20 nm to obtain nano-modified aluminum sulfate particles.